2017
DOI: 10.1021/acs.nanolett.6b04816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Fluctuations on the Radiative Rate in Core/Shell Quantum Dots

Abstract: The effect of lattice fluctuations and electronic excitations on the radiative rate is demonstrated in CdSe/CdS core/shell spherical quantum dots (QDs). Using a combination of time-resolved photoluminescence spectroscopy and atomistic simulations, we show that lattice fluctuations can change the radiative rate over the temperature range from 78 to 300 K. We posit that the presence of the core/shell interface plays a significant role in dictating this behavior. We show that the other major factor that underpins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 81 publications
(145 reference statements)
3
47
0
Order By: Relevance
“…To acquire more intrinsic characteristics of the photogenerated excitons in the high color-purity NBE-T-CQDs, temperature-dependent PL spectra were also recorded, and the resulting emission narrowing was analyzed, as has long been used to assess mechanisms of electron–phonon coupling in a wide range of bandgap emitting inorganic QDs 44 , 45 . As the temperature is decreased from 295 to 85 K, all the PL peaks of the NBE-T-CQDs show continuous narrowing and blue-shift (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To acquire more intrinsic characteristics of the photogenerated excitons in the high color-purity NBE-T-CQDs, temperature-dependent PL spectra were also recorded, and the resulting emission narrowing was analyzed, as has long been used to assess mechanisms of electron–phonon coupling in a wide range of bandgap emitting inorganic QDs 44 , 45 . As the temperature is decreased from 295 to 85 K, all the PL peaks of the NBE-T-CQDs show continuous narrowing and blue-shift (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2g , the FWHM reduces from 164.7 (30 nm) to 95.4 meV (16 nm) and the emission peak energy of the B-NBE-T-CQDs shifts toward higher energy from 2.627 to 2.725 eV with decreasing temperature from 295 to 85 K. The narrowed FWHM and blue-shifted emission peaks of the NBE-T-CQDs with decreasing temperature are well described by traditional empirical Varshni models, which can be explained by the reduced electron–phonon coupling due to the restricted structural vibrations and distortions at the lower temperatures 44 – 46 . It has been demonstrated that the electron–phonon coupling resulting from structural vibrations and distortions plays a dominating role in determining the FWHM of the PL spectra of inorganic QDs 44 , 45 . Therefore, it is reasonable to conclude that the dramatically reduced electron–phonon coupling demonstrated by the temperature-dependent PL spectra leads to the high color-purity, free-excitonic emission of the NBE-T-CQDs.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy relies on the fact that the QD emission peak energy is temperature dependent and furthermore is approximately linear in temperature over the 80−300 K range. 41 We could therefore place a 78 K sample into an integrating sphere and record PLQYs while the sample warmed to RT and then use the emission peak energy to determine the corresponding temperature. This process was repeated 5−7 times for each sample to obtain accurate PLQY vs temperature data.…”
Section: Resultsmentioning
confidence: 99%
“…Indium phosphide QDs have garnered significant interest as a cadmium-free option that is tunable throughout the visible wavelength regime (Micic et al, 1994 ; Guzelian et al, 1996 ; Battaglia and Peng, 2002 ; Xie et al, 2007 ; Li and Reiss, 2008 ; Xu et al, 2008 ; Tamang et al, 2016 ). As-synthesized InP QDs, however, are non-emissive due to non-radiative relaxation of excitation generated charge carriers facilitated by trapping at surface defects (Dennis et al, 2012a ; Omogo et al, 2013 ; Balan et al, 2017 ; Reid et al, 2018 ). Fabrication of emissive cores can be performed through two main synthetic routes: etching the surface of the nanoparticle using a fluoride, or overcoating with a larger bandgap semiconductor to create a core/shell heterostructure (Danek et al, 1996 ; Dabbousi et al, 1997 ; Talapin et al, 2002 ; Adam et al, 2005 ; Chen et al, 2013 ; Mordvinova et al, 2014 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%